ANALISIS DAMPAK COVID-19 BAGI UMKM DI JAWA TIMUR - Aisyah Aminy; Kartika Fithriasari (Seminar Nasional Official Statistics, 2020)
The covid-19 pandemic that is currently happening has had an impact on various sectors. At the global economic level, the covid-19 pandemic has very significant impact on the domestic economy where this condition has been seen in the economic growth of East Java which grew by 3,04 percent in the first quarter, far from the average in the same period which was 5 percent. This condition is also experienced by micro, small and medium enterprises (MSMEs) in East Java. The slowdown in economic growth in East Java due to covid-19 has had a major impact on MSMEs, where from 2016 until 2018 MSMEs contributed more than 50 percent to the East Java economy. Therefore, research is needed on the impact of covid-19 for MESMEs in East Java so that policy steps can be taken in determining empowerment program recommendations during a pandemic. The data collection method was carried using an online survey of MSME players in East Java in various sectors by means of nonprobability sampling. From the survey results obtained 31.183 data where there are 4 (four) main sectors affected, namely the processing industry, the provision of accommodation and food and drink, trade, as well as agriculture, forestry and fisheries. Furthermore, the identification of problems with affected MSMEs was carried out, where 48 percent experienced problems with sales. This is because there are several policies taken by the Government, namely Large-Scale Social Restrictions (PSBB), Work From Home (WFH), and School From Home (SFH), causing changes in community mobility as indicated by the decreasing community mobility index. Therefore, the recommendation that can be given is online marketing assistance for MSMEs and financing access facilities.